DEVELOPMENT OF A BUGIS LANGUAGE DICTIONARY APPLICATION WITH SM-KMP ALGORITHM FOR STUDENTS IN SOUTH SULAWESI - M, Effendi; Juhardi, Juhardi; Ahmad, Muhammad Sabri; Zainuddin, Zainuddin (Universitas Khairun, 2025)
The decline in the use of the Bugis language among younger generations in South Sulawesi poses a significant challenge in preserving local languages and cultures. One solution to this issue is developing a Bugis language dictionary application based on technology, which can interactively facilitate language learning. This study aims to develop a Bugis language dictionary application using the Knuth-Morris-Pratt (SM-KMP) algorithm to improve the efficiency of word searches within the dictionary. The research method involves application development with a prototype tested in South Sulawesi schools. This application is designed with features for fast and accurate word searches and interactive elements such as quizzes and educational games to enhance student motivation in learning the Bugis language. The results show that the application improved students' vocabulary comprehension by 85%, and 90% reported increased motivation to learn Bugis due to the interactive features. The application also supports preserving local culture by integrating character education that teaches ethical values and local wisdom in Bugis. In conclusion, this Bugis language dictionary application based on the SM-KMP algorithm is practical as an interactive learning tool. It holds significant potential in preserving the Bugis language and culture